2021
DOI: 10.21608/aimj.2021.63309.1419
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Indices Of Vascular Cognitive Impairment After Stroke In a Sample Of Egyptian Patients

Abstract: Background:The second prevalent cause of death globally is cerebrovascular stroke. It's responsible for a great extent of disabilities than any other condition. A large share of this disability is related to poststroke neurocognitive impairment. Aim of the study: This study aimed to assess neuroimaging indices related to cognitive dysfunction in a sample of Egyptian stroke patients. Patients and Methods: This study included 70 patients diagnosed with ischemic or hemorrhagic stroke after 3 months from the onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Furthermore, Osama et al [24] concluded that hypertension was the primary risk factor for cardiovascular disease in Egypt. These findings are also supported by a study by Essmat et al [25] , which found that the incidence of stroke increases with age and that risk factors for stroke include older age, hyperlipidemia, diabetes mellitus, and hypertension. In terms of residence, the study found that over two-thirds of patients in both groups were from rural areas.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, Osama et al [24] concluded that hypertension was the primary risk factor for cardiovascular disease in Egypt. These findings are also supported by a study by Essmat et al [25] , which found that the incidence of stroke increases with age and that risk factors for stroke include older age, hyperlipidemia, diabetes mellitus, and hypertension. In terms of residence, the study found that over two-thirds of patients in both groups were from rural areas.…”
Section: Discussionsupporting
confidence: 77%
“…To the best of our knowledge, this is the first study of its kind in Compared to different eastern and western countries, PSCI rate at acute phase in Lebanon is one of the highest rates, similar to the rates in Shanghai, China (88.1%) (Li et al, 2020), and South Korea (69.8%) (Yu et al, 2013), but greater than the rates obtained in USA, France, Britain, Australia, Sweden, India, Norway, Singapore, Nigeria, and Egypt that range between 20% and 50% (Akinyemi et al, 2014;Essmat et al, 2021;Sun et al, 2014). This variability might be explained by the difference in countries, race, and the used diagnostic criteria, in addition to different factors reported in the present study.…”
Section: Discussionmentioning
confidence: 69%